If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(x + -2)(x + 3) = 0 Reorder the terms: -2(-2 + x)(x + 3) = 0 Reorder the terms: -2(-2 + x)(3 + x) = 0 Multiply (-2 + x) * (3 + x) -2(-2(3 + x) + x(3 + x)) = 0 -2((3 * -2 + x * -2) + x(3 + x)) = 0 -2((-6 + -2x) + x(3 + x)) = 0 -2(-6 + -2x + (3 * x + x * x)) = 0 -2(-6 + -2x + (3x + x2)) = 0 Combine like terms: -2x + 3x = 1x -2(-6 + 1x + x2) = 0 (-6 * -2 + 1x * -2 + x2 * -2) = 0 (12 + -2x + -2x2) = 0 Solving 12 + -2x + -2x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(6 + -1x + -1x2) = 0 Factor a trinomial. 2((2 + -1x)(3 + x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2Subproblem 2
Set the factor '(3 + x)' equal to zero and attempt to solve: Simplifying 3 + x = 0 Solving 3 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + x = 0 + -3 x = 0 + -3 Combine like terms: 0 + -3 = -3 x = -3 Simplifying x = -3Solution
x = {2, -3}
| .3x+1.7=.2x-.4(5x+1) | | 5c/3c-1 | | 2x+6/x-9=0 | | 8x^2-38x-10=0 | | .3(x-2)+.4x=.2(x-6) | | 2(x-4)=5/6(x+6)-6 | | 3x-23=97-9x | | 1/5(y+2)=1/10y+3/5 | | 2x-4+7=-6x+41 | | 3x-2(x-4)=8-2x+15 | | -3-4x=5x+24 | | 5-(1/2)x=(1/8)x | | 5x^2-4x+3=6 | | 11c=9c+14 | | 2-2x-5/5=x+9/4 | | 12x-3x-7=11 | | 56-s=45-9 | | 1+(3*7)=z | | 1+(3*7)= | | 1/2-1=1/44 | | -24p^2q^2+(-2pq)+3= | | 2x-6x+21=-13 | | -4x+21=-13 | | 28x+4+7x+7=102 | | 1xy=78 | | 1*y=787 | | 1y=78 | | xy=-40 | | ax+5x-4=10 | | 4-4x^2+4xy-y^2= | | 15-1/2x=1/4x | | x/5-x/3=8/15 |